2011
DOI: 10.5539/ijel.v1n2p91
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of English be Auxiliary and Thematic Verb Constructions by Adult Arab ESL Learners

Abstract: This study investigates the acquisition of English be auxiliary and thematic verb constructions in non-past contexts by adult Arab learners of English as a Second Language (ESL). It is well known that second language (L2) learners show variability in the L2 production of verbal inflectional morphology by either omitting inflections or marking inappropriate substitution of one kind of inflection for another. The Missing Surface Inflection Hypothesis (MSIH) (Prévost and White, 2000) proposes that L2 learners hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This result is similar to Alshayban's (2012) results where the copula "be" errors were found in his participants' compositions. The copula "be" errors were also found in research done by Muftah and Eng (2011) where they were more prevalent than 3 rd person morpheme errors, while in my study there was no significant difference between them (the copula "be" = 21, the 3 rd person morpheme =22). The copula "be" errors were not found in the compositions of the non-Arabic participants.…”
Section: -Errors Of the Copula "Be"supporting
confidence: 57%
See 1 more Smart Citation
“…This result is similar to Alshayban's (2012) results where the copula "be" errors were found in his participants' compositions. The copula "be" errors were also found in research done by Muftah and Eng (2011) where they were more prevalent than 3 rd person morpheme errors, while in my study there was no significant difference between them (the copula "be" = 21, the 3 rd person morpheme =22). The copula "be" errors were not found in the compositions of the non-Arabic participants.…”
Section: -Errors Of the Copula "Be"supporting
confidence: 57%
“…The researchers found that the subjects committed errors using the third person morpheme. In another study, Muftah and Eng (2011) tested the missing surface inflection hypothesis (MSIH) (Prevost & White, 2000, cited in Muftah andEng, 2011), which claims that L2 learners do not map and match functional classifications and features of tense and agreement correctly although…”
mentioning
confidence: 99%
“…Guasti (2002, p. 120) has claimed that finite verbs are generally associated with tense and agreement features. In other words, tense feature of finite clauses are morphologically specified as either past or present tense i.e., finite verbs must be spelled out into features that can capture the difference (Muneera and Wong, 2011). For example, in (2), the present tense feature of the verb is spelled out as the 3sg -s.…”
Section: The Present Simple Tense In Englishmentioning
confidence: 99%
“…In this case, we need to appropriate verb form, i.e., the finite verb with the affixal or 3sg -s (4b) (see e.g., Muneera and Wong, 2011). (4) a.…”
Section: The Present Simple Tense In Englishmentioning
confidence: 99%
“…Prior research on this population (e.g. Muftah, & Eng, 2011) has indicated that Arab ELLs often omit verb to BE when they produce English utterances.…”
Section: Characteristics Of the Modal Expressionsmentioning
confidence: 96%